A novel splicing mutation in the PROS1 gene causes hereditary protein S deficiency in a Chinese family with thrombotic disease. Issue 189 (May 2020) - Tan, Ya; Yang, Kai; Wang, Jing; Sun, Xinping; Li, Ruirui; Dong, Zhe; Zhao, Na; Yan, Yousheng; Lin, Li
Highlights: A heterozygous splicing variation PROS1 : c.965 + 4A > T was found in a family with venous thrombosis. PROS1 : c.965 + 4A > T splice site variant activated a cryptic donor site located inside exon 9, leading to the deletion of the last 78 nucleotides of PROS1 mRNA exon 9. The deletion in exon 9 causes the loss of 26 protein S amino acid residues that border the Laminin_G_1 domain.